콩 주요 품종에 대한 점무늬병 저항성 평가 - 강인정(In Jeong Kang); 심형권(Hyeong Kwon Shim); 신동범(Dong Bum Shin); 노재환(Jae Hwan Roh); 고재덕(Jaeduk Goh); 허성기(Sunggi Heu) (Sigmulbyeong yeon'gu, 2015)
Soybean frogeye leaf spot caused by the fungus Cercospora sojina Hara, has known to lead a severe reduction of crop yield. Since frogeye leaf spot on soybean has recently become a serious problem in Korea, the susceptibility of recent recommended cultivars against C. sojina had been tested. To standardize the disease severity of soybean, the optimum sporulation condition of C. sojina and the disease index were established in this study. Sporulation was maximized on the 10% V8 juice agar with 12 h light and 12 h dark at $25^{°}C$. Spore suspension ($10^5spores/ml$) was sprayed on the leaves of soybean (V6 stage), and the disease responses to each isolate were evaluated on 28 days after inoculation. As a result, Daepung, Shinpaldal2ho, Yeonpung and Cheonga showed the resistance reaction to 8, 7, 6, 6 isolates of C. sojina, respectively, whereas Cheongja, Hwangkeum, Taekwang, Daewon, Cheonsang and Sinhwa showed the susceptible reaction to 8 isolates of C. sojina. Breeding the resistant soybean cultivars against C. sojina requires a uniform resistance for screening technique. The disease index of frogeye leaf spot on soybean developed in this study can be effectively used for the accurate field assay to select the frogeye leaf spot resistant soybean. 점무늬병은 콩에서 최대 50% 정도의 수량감소가 보고된 병으로 최근 한국 콩 재배포장에서 큰 문제로 대두되고 있어 최근 6년간의 보급 품종을 대상으로 콩 점무늬병에 대한 저항성 검정을 실시하였다. 표준화된 검정방법을 적용하기 위해 가장 효과적인 포자 형성 배지 조건을 탐색하고 저항성 검정 평가 기준을 확립하였다. 포자형성은 $25^{°}C$, 12시간 광 조건과 암 조건에서 V8 juice를 이용한 배지의 포자 형성이 가장 효과적임을 알 수 있었다. 접종은 $10^5spores/ml$로 준비하여, 제 5 복엽 완전전개기인 V6 stage까지 키운 건강한 콩 식물체에 실시하였고 병 반응은 28일 동안 관찰하였다. 그 결과 대풍은 8개 균주 모두 저항성을 보였고, 신팔달2호는 7개 균주에, 연풍, 청아는 6개 균주에 저항성을 보였다. 반면에 황금, 태광, 대원, 천상, 신화 등은 평가한 8개 균주에 모두 감수성 반응을 나타내었다. 콩 점무늬병에 대한 저항성 품종을 육종하기 위해 표준화되고 정밀화된 저항성 검정방법과 판정 체계를 갖추는 것은 매우 중요하며 이 방법은 차후 포장 저항성 검정에도 적용할 수 있을 것이라 기대한다.